A interatividade nos museus de ciências: o processo de criação de um artefato museal - Ferreira, Gustavo Lopes (2014)
The present research begins by verifying the almost inexistence of studies that show how the exhibits and the objects of a science museum are produced, also arises from involvement with the modernization project of the Museu de Biodiversidade do Cerrado-MBC. We aimed to create an interactive artifact inserted in MBC\'s exhibition, presenting and analyzing the main aspects of this creative process. And we seek to study the object created through the visiting public, investigating their behavior while interacting with the artifact. We thought in the museum\'s object using the concepts of artifact, interactivity and aesthetic experience. We understand the artifact as an object produced by man, designed according to the principles of interactivity to function disseminating scientific knowledge in the exhibits of a science museum. Interactivity was a possibility found to approach the public and the exhibition, through various interactions, physical, intellectual, and emotional over all. Intended to arouse the emotions that we think about aesthetic experience, which has to do with the way in which the person is affected, touched, get emotioned and produces interaction with the artifact.The theme of the artifact is Ornithology, to present it were projected interactive and artistic objects that provides an experience using the senses. When performing the discrete observations in the study of MBC\'s spontaneous public, we perceive behaviors, visitor\'s reactions and speeches, denoting that the contact with the artifact allowed more than an intellectual experience with scientific knowledge and enabled an aesthetic experience, allowed by emotions. Through research we can better understand the commitment of museums in cultural formation of individuals, who through unique experiences can broaden your worldview.